2020
DOI: 10.1002/jccs.202000046
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of phase transformation behaviors of zeolite and antibacterial properties against Gram‐positive and ‐negative bacteria

Abstract: This study deals with the synthesis of zeolite from natural kaolinite using hydrothermal treatment and evaluation of its phase transformation behaviors. The synthesized zeolites were modified with silver ion by using the ion exchange method for the enhancement of antibacterial properties. The characterizations were performed by using X-ray diffraction spectroscopy, Fouriertransform infrared spectroscopy, field emission scanning electron microscopy, and energy-dispersive X-ray. Disk diffusion technique (DDT) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
0
1
0
Order By: Relevance
“…From the trend, CS150 with a high amount of Ag-loaded clinoptilolite (150% of the CEC of the Cli) showed the highest antibacterial activity. Thus proving that the antibacterial activity of the modified zeolite was contributed by the Ag [14]. Furthermore, this sample (CS150) had higher antibacterial activity than CS40 which had a lower Ag amount loaded Cli.…”
Section: Antibacterial Activitymentioning
confidence: 80%
“…From the trend, CS150 with a high amount of Ag-loaded clinoptilolite (150% of the CEC of the Cli) showed the highest antibacterial activity. Thus proving that the antibacterial activity of the modified zeolite was contributed by the Ag [14]. Furthermore, this sample (CS150) had higher antibacterial activity than CS40 which had a lower Ag amount loaded Cli.…”
Section: Antibacterial Activitymentioning
confidence: 80%
“…Kaolinite is already an ideal raw material with the same Si/Al ratio, and quartz only reduces the relative crystallinity of the zeolite, 54 contaminates the product or dissolves. 23,121,122 On the contrary, in the synthesis of zeolites with a higher Si/Al ratio, quartz, provided it dissolves, can be an additional source of SiO 2 . 61,123 Mohiuddin et al have reported that quartz deposits on the surface of ZSM-5 during the synthesis and acts as a promoter in the oligomerisation of hexene-1.…”
Section: Kaolin Pretreatment Methodsmentioning
confidence: 99%